Unusual manifestations of Epstein-Barr virus infection in an 8-month-old male infant - Peninnah Oberdorfer (2018)
Severe acute hepatitis is a rare complication of Epstein-Barr virus (EBV) infection. The authors report a case of an 8-month-old male infant who presented with subacute fever and jaundice. The physical examination showed hepatosplenomegaly and ecchymoses on his abdomen, chest wall and extremities. He received vitamin K therapy and prednisolone, and he recovered well without further complications or sequelae. Although severe acute hepatitis is a rare complication of EBV infection, clinicians should recognise this condition in order to provide a prompt treatment.